2016
DOI: 10.1038/onc.2016.402
|View full text |Cite
|
Sign up to set email alerts
|

ROCK2/rasHa co-operation induces malignant conversion via p53 loss, elevated NF-κB and tenascin C-associated rigidity, but p21 inhibits ROCK2/NF-κB-mediated progression

Abstract: ROCK2/rasHa cooperation induce malignant conversion via p53 loss, elevated NF-κβ and tenascin C-associated rigidity but p21 inhibits ROCK2/NF-κβ-mediated progression. Oncogene, 36, pp. 2529Oncogene, 36, pp. -2542Oncogene, 36, pp. . (doi:10.1038Oncogene, 36, pp. /onc.2016 This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/129163/ Malignancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…8). An involvement of NF-κB in SCC initiation and progression in vivo was previously demonstrated [37,38]. Since KPNA4 functions as a transporter for these two oncoproteins, how these TFs coordinate in the evolution of SCC should be examined in future studies.…”
Section: Discussionmentioning
confidence: 88%
“…8). An involvement of NF-κB in SCC initiation and progression in vivo was previously demonstrated [37,38]. Since KPNA4 functions as a transporter for these two oncoproteins, how these TFs coordinate in the evolution of SCC should be examined in future studies.…”
Section: Discussionmentioning
confidence: 88%
“…Targeting ROCK2 and oncogenic RAS to mouse epidermis enhanced malignant conversion associated with loss of p21. 51 Similarly, while epidermal deletion of RhoA increased skin tumor incidence, it encouraged tumor invasion through a compensatory increase in cutaneous RhoB. 52 These data suggested that Rho/ROCK signaling can have differential effects on benign and malignant tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…ROCK activation is positively associated with tumor growth (13,(41)(42)(43), and a growing number of studies continue to lend credence to the importance of the ROCK signaling pathway in lung cancer development. ROCK is one of the Rho pathway genes that is significantly upregulated in a number of KRAS mutant NSCLC cell lines (44,45), several NSCLC animal models (15,46), and tumor tissues derived from patients with NSCLC (37,47).…”
Section: Rock Signaling Pathway and Expression In Lung Cancermentioning
confidence: 99%
“…ROCK plays an essential role in carcinogenesis, particularly in promoting cancer cell motility that causes metastasis. ROCK is an effector of the small GTPase Rho and has been studied in various malignancies, such as breast (12), skin (13), liver (14) and lung cancer (15). Studies on lung cancer usually use NSCLC cell lines or tissue biopsies from patients with NSCLC to assess changes in the proliferation, migration, and growth of cancer following the inhibition of knockdown of ROCK (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%